2020
DOI: 10.12659/msm.924625
|View full text |Cite
|
Sign up to set email alerts
|

miR-18a-5p Promotes Proliferation and Migration of Vascular Smooth Muscle Cells by Activating the AKT/Extracellular Regulated Protein Kinases (ERK) Signaling Pathway

Abstract: Background microRNAs (miRNAs) play important roles in abnormal proliferation and migration of vascular smooth muscle cells (VSMCs), which lead to restenosis in coronary artery disease. Nevertheless, the role of miR-18a-5p and how it works in VSMCs remain unknown. Material/Methods miR-18a-5p expression was determined by fluorescence quantitative real-time polymerase chain reaction (qRT-PCR) analysis of tissues from 20 patients with stent restenosis, and rats with carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…We have shown for the first time that miR-18a-5p in CFU-Hill’s colonies is upregulated in T1DM. MiRNA-18a-5p has been suggested to serve an important role in various biological activities leading to the pathogenesis of vascular diseases, as significantly upregulated miRNA-18a-5p was previously reported in the serum of patients with stent stenosis and in animal models with carotid artery injury [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown for the first time that miR-18a-5p in CFU-Hill’s colonies is upregulated in T1DM. MiRNA-18a-5p has been suggested to serve an important role in various biological activities leading to the pathogenesis of vascular diseases, as significantly upregulated miRNA-18a-5p was previously reported in the serum of patients with stent stenosis and in animal models with carotid artery injury [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that the dysregulation of multiple miRNAs is responsible for the pathogenesis of CVD. The overexpression of miRNA-18a-5p has been identified as pro-atherogenic miRNA as it promotes proliferation and migration of vascular smooth muscle cells [ 25 , 26 ]; moreover, an animal model of oxygen-induced proliferative retinopathy revealed that the overexpression of miR-18a-5p in human retinal microvascular endothelial cell, was anti-angiogenic as inhibited angiogenesis via significant downregulation of fibroblast growth factor-1 and hypoxia-inducible factor-1 alpha (HIF-1α), which are both closely associated with angiogenesis [ 27 ]. The anti-angiogenic property of miR-18a-5p renders it an ideal candidate for studying the paracrine function of CFU-Hill’s colonies.…”
Section: Introductionmentioning
confidence: 99%
“…To better define the molecular mechanisms by which this ARF isoform controls HASMC invasive capabilities, we aimed to identify the different downstream signaling events. In previous studies, PDGF-BB was shown to activate mitogenic cascades, which have been previously associated with VSMC invasion [17][18][19][20] . Here, we therefore first examined whether invasion was modulated by activation of the ERK1/2 pathway.…”
Section: Pdgf-bb and Ang II Promote Cell Invasion Via An Arf6-dependent Mapk Activationmentioning
confidence: 86%
“…It has been reported that both miRNAs [36] and lipoproteins such as HDL [37] could regulate many of the key processes involved in atherosclerosis [38]. Thus, the association between the expression of miRNAs related to the PBMCs [39], VSMCs [40][41][42][43], and vascular endothelial cells [44][45][46] with cardiovascular disease (CVD) and restenosis has been previously discussed [26,39,44]. However, to the best of our knowledge, there is no study that showed the serum expression level of miRNAs related to lipoproteins and lipid metabolism in ISR patients.…”
Section: Discussionmentioning
confidence: 99%